Habitat et espace commercial. Le modèle architectural mixte des "petits grands magasins" Gonset, 1925-1970 - Jornod, Joël (My University, 2014)
Department stores are famous for their magnificent architecture. Their luxurious multistorey buildings totally dedicated to consumption have often been emphasized in historiography. However, such studies are heavily concentrated upon the biggest and most famous companies of the Western metropolises. This paper highlights another architectural form which was used by smaller firms in little towns and important villages. These “small department stores” combined housing and commercial space in the same buildings. This article presents a case study of Gonset, a family business that operated such stores across western Switzerland. It shows that between 1925 and 1970 the majority of Gonset’s stores included apartments. This mixed architectural form is due to three factors: legislation hindering the development of department stores and chains (1933–1945), laws protecting tenants, and Gonset’s strategy for diversifying revenue sources by leasing dwellings. This combining of housing and rental space had an impact on Gonset’s corporate identity. It conferred on the firm a sober style reminiscent of traditional shops. This style was in stark contrast with the culture of excess of big department stores.
Keywords: Consommation; commerce de détail; distribution; architecture